Exploring the Relationship between Prophetic Leadership and Job Satisfaction of Madrasah Ibtidaiyah Teachers in Indonesia - Juhji, Juhji; Rahmatullah, Mamat; Noor, Wahyudin; Zuhri, Saefudin; Mansur, Mansur; Nuangchalerm, Prasart (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study examined the relationship between prophetic leadership and job satisfaction among Madrasah Ibtidaiyah teachers in Indonesia. The research method used a quantitative research design with survey techniques. Data were collected from 179 facilitator teachers in 27 provinces using a validated Likert scale questionnaire. Data analysis used regression tests to assess the effect of prophetic leadership on job satisfaction. Findings showed a significant positive correlation, indicating that a 1% increase in prophetic leadership was associated with a 0.514 increase in job satisfaction. It suggests that enhancing the principles of prophetic leadership within an education management framework can significantly improve teachers' well-being and the overall quality of education in Madrasah Ibtidaiyah. This study underscores the importance of integrating moral and spiritual dimensions into Islamic education, encouraging a more inclusive and dignified work environment for educators. The implications of the findings advocate a shift towards a leadership model that prioritizes ethical considerations, potentially leading to sustainable improvements in educational practices and outcomes.